(untitled) (Research, Society and Development, 2022)
Aging is inevitable, it is a biological process and always a constant, which is caused by natural factors and external agents. In addition, it is essential to note that the look can change according to aging. Based on this assumption, studies for eyelid surgery, known as blepharoplasty, began. Due to new aesthetic needs, an instrument with a new technology was introduced in this environment, called electrocautery. He is able to make interventions through small and controlled electrical discharges, in order to remove tissue. In this sense, for those who are bothered by the drooping of the upper eyelid, this aesthetic procedure is highly recommended because it is not an invasive method, because it has a low cost and because it is a great adjunct to other treatments in order to improve the area even more. such as botulinum toxins and support threads. Thus, the present article aims to complement studies on the treatment of the upper eyelid through electrocautery and plasma jet through a clinical case. It can be concluded that the use of electrocautery brings benefits and advances in aesthetic treatments, and that, with the help of an anti-inflammatory therapy, it is possible to successfully treat cases of palpebral ptosis.